2010
DOI: 10.3109/09593980802640059
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hydrotherapy on skin blood flow: How much is due to moisture and how much is due to heat?

Abstract: Hydrotherapy and whirlpool are used to increase skin blood flow and warm tissue. However, recent evidence seems to show that part of the increase in skin blood flow is not due to the warmth itself but due to the moisture content of the heat. Therefore, two series of experiments were accomplished on 10 subjects with an average age of 24.2 +/- 9.7 years and free of diabetes and cardiovascular disease. Subjects sat in a 37 degrees C hydrotherapy pool under two conditions: one in which a thin membrane protecting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Movement of heat to or from the skin is through the passive heat exchange properties of the skin and the ability of the circulation to change [9]. Skin circulation is controlled through the sympathetic nervous system [10], mediated by vascular endothelial cells releasing vasodilators such as nitric oxide [11]. When local heat is applied to the skin, these same vasodilators respond to increase skin circulation and protect the skin from damage [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Movement of heat to or from the skin is through the passive heat exchange properties of the skin and the ability of the circulation to change [9]. Skin circulation is controlled through the sympathetic nervous system [10], mediated by vascular endothelial cells releasing vasodilators such as nitric oxide [11]. When local heat is applied to the skin, these same vasodilators respond to increase skin circulation and protect the skin from damage [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…The heat modality used most commonly clinically is hydrocollator heat wraps. 30 This local heat source reduces cytokines and pain. [31][32][33] However, hydrocollator heat wraps are a clinical tool that cannot be used at home.…”
Section: Introductionmentioning
confidence: 99%
“…Two widespread heat modalities were used: a clinical heat modality, hydrotherapy, 43 and a common home modality, ThermaCare dry heat. [3][4][5] However, recent experiments published in the last few years showed that chemically generated moist heat is more effective in warming deep tissue than that seen with either of these standard therapy modalities, 30,36,37 and that is why all three modalities were tested in this study. This is highly relevant because chemical moist heat packs have not been tested on muscle soreness in people with diabetes.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…One of those was through conductive heat loss. Conductive heat loss, as described above, involves passive properties of the skin including skin fat content, moisture, and structure [ 64,85 ] . The other way of moving heat is related to skin blood fl ow [ 81 ] .…”
Section: Modeling Of Heat Exchange Through the Skinmentioning
confidence: 99%